A New High Order Virial Equation of State and Its Application in the Chapman‐Jouguet Parameters Calculation of Explosives. Issue 1 (22nd July 2022) - Peng, Yue; Long, Xinping; Jiang, Xiaohua; Zhang, Zhiming
Abstract: In this paper, in order to solve the deficiency of VLW (Virial‐Wu) equation of state (EOS) and VHL (Virial‐Han‐Long) EOS in describing thermodynamic relationship in high temperature region of gaseous detonation products. Based on the Mayer expansion theory of gas virial coefficients in statistical mechanics, the fourth‐order and fifth‐order dimensionless virial coefficients for Lennard‐Jones (L−J) 6–12 pair potential in a higher temperature range are calculated by using the orthogonal integral method which proposed by Barker. By fitting the theoretical calculation values, a new high order virial EOS: VPL (Virial‐Peng‐Long) EOS for gaseous detonation products is established. Implanting the VPL EOS with the properly introduced EOS of condensed carbon and condensed metal products into the detonation thermodynamic program, the Chapman‐Jouguet (CJ) detonation parameters including detonation velocity, detonation CJ pressure, and detonation temperature of some typical CHNO high explosives and some metal‐containing primary explosives are calculated and obtained. By comparing the calculated values with the experimental values, as well as the calculation values obtained by VLW EOS, VHL EOS, and EXPLO5 (using BKWG−S EOS) software, the accuracy and applicability of VPL EOS in CJ detonation parameters calaulation are analyzed and evaluated. Abstract :